Religion, the public sphere, and identity politics: how a radical Muslim organization defies the populist right in Switzerland. Issue 5 (20th October 2017) - Sheikhzadegan, Amir; Nollert, Michael
ABSTRACT: The increasing visibility of Islam and the advance of right-wing anti-immigration politics in Switzerland have led to conflicts between assimilationists and Islamists. By focusing on two protagonists of this conflict – the populist right-wing Swiss People's Party (SVP) and the Islamist organization Islamic Central Council Switzerland (IZRS) – we deliver an analysis of their strategies and counter-strategies. We argue that the public visibility of Islam has become the main contested issue between both parties. Whereas the former strives for containing 'the Islamic threat' by pushing Islam out of the public sphere, the latter uses public visibility of Islam to establish this religion as an integral part of Swiss society. We further argue that both parties resort to well-developed boundary-making identity politics to either consolidate their collective identity (the IZRS) or to stigmatize the opponent (the SVP). We also show that both parties actively engage in constructing internally homogeneous and externally exclusive imagined communities.